Patronal Feast as a Symbol of Mayordomo’s ‘Purchasing Power’ in Huanta, Peru - Gutiérrez-Gómez, Edgar; Urpay-Lapa, Janeth Keyko; González-Ríos, Rosa Cecilia; Aspur-Barrientos, Jaime Carmelo; Auccatoma-Tinco, Roly (Millah: Journal of Religious Studies, 2025)
This is a qualitative study of a religious event of great importance in the community, where the mayordomo assumes a central role, not only as a spiritual leader, but also as a symbol of purchasing power. The objective of this research is to examine how the organization of the festival reflects the economic status of the mayordomo, who is forced to finance various aspects of the event in order to maintain his prestige within the community. For this purpose, a qualitative methodology is used, employing narrative analysis and discourse analysis. Through interviews with stewards and participants, narratives and discourses are identified that highlight how the position of stewardship is a manifestation of economic power and social respect. In conclusion, the festival not only has a religious value, but also a great economic and social significance, where the mayordomo exhibits his status through his ability to finance and organize the festivity, reaffirming his position within the community.